CULTURAL PECULIARITIES OF THE BRITISH, ITALIANS AND TATARS IN PHRASEOLOGICAL UNITS - (:unkn) unknown (INST INTEGRATIVE OMICS & APPLIED BIOTECHNOLOGY, 2018)
This article is devoted to the description of phraseological units, reflecting national and cultural characteristics of the British, Italians and Tatars. In the process of the comparative analysis were revealed similarities and differences of the studied phraseological units. The system of images fixed in the semantics of the national language is the sphere of the concentration of cultural information in the natural language. Phraseological units that characterize a person, as well as his behaviour in different situations, represent a fairly large group and are used more often. Phraseological units serve as the means of accumulating and transferring standards and stereotypes of national culture. All the material and spiritual values developed by mankind for centuries and characteristic of the culture of a certain community are reflected and preserved in phraseological units. The peculiarity of the author's use of phraseological units is manifested in the fact that phraseological units are transformed by various methods. The practical significance of studying this problem lies in the fact that the study of unrelated heterogeneous languages makes it possible to apply the results of the study in teaching the English, Italian, Tatar languages, in linguoculturology courses, cross-cultural studies, phraseology and compilation of phraseological dictionaries.
Keywords: phraseologisms; comparative analysis; foreign language; English; Tatar; Italian languages